Pendampingan Berbasis Aset Pada Masyarakat Pedagang : Peluang Pengembangan Perdagangan Sawo Dusun Bunut Desa Bringin Kecamatan Badas Kabupaten Kediri - Asror, Khozinatul; Salahuddin, Nadhir (Journal of Islamic Community Development, 2021)
This is a report of empowerment effort to sapodilla fruit sellers in Bunut Bringin village. The location of selling the fruit is relatively strategic as it is at the main road where many traveler passing by. The location obviously helps communities of sapodilla fruit sellers, however it is insufficient to attract more people in order to have more income from the selling. The sellers have tried to find a way to increase their income not just by selling the fruit, but also selling food that made of this fruit, like jam. But this was unsuccessfully, the sellers not satisfied with the product as the flavor of the fruit disappear when it is transformed into jam. They, then, reluctant to try and innovate the product. The disappointed sellers is, then, focus of this work. Using Asset-based Community development (ABCD) approach, this work has motivated the sellers to mobilize their own strength to open opportunity to make betterment of their life. Appreciative inquiry was used to nurture agency among the sellers, and it was also successfully to bring more cohesiveness. The approach has had successfully to make people realized that despite all the challenges, there are still widely open opportunity regarding sapodilla fruit selling efforts. This is very much in accordance with the teaching of Islam that in Qur’an Allah says that Allah will not change the condition of the people unless they make the effort. It is also a prove that in the work of community development, changing the mindset of the people is really at the center of the transformative change.